NUSAP1 Could be a Potential Target for Preventing NAFLD Progression to Liver Cancer - Zeng, Taofei; Chen, Guanglei; Qiao, Xinbo; Chen, Hui; Sun, Lisha; Ma, Qingtian; Li, Na; Wang, Junqi; Dai, Chaoliu; Xu, Feng (Frontiers in Pharmacology, 2022)
Abstract Background: Non-alcoholic fatty liver disease (NAFLD) has gradually emerged as the most prevalent cause of chronic liver diseases. However, specific changes during the progression of NAFLD from non-fibrosis to advanced fibrosis and then hepatocellular carcinoma (HCC) are unresolved. Here, we firstly identify the key gene linking NAFLD fibrosis and HCC through analysis and experimental verification. Methods: Two GEO datasets (GSE89632, GSE49541) were performed for identifying differentially expressed genes (DEGs) associated with NAFLD progression from non-fibrosis to early fibrosis and eventually to advanced fibrosis. Subsequently, Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways enrichment analysis, protein-protein interaction (PPI) network were integrated to explore the potential function of the DEGs and hub genes. The expression of critical genes was confirmed in vivo and in vitro NAFLD models. Then, the expression of essential genes was confirmed through the sequencing dataset GSE16444, IHC from the HPA website and validation in vitro. Finally, the analysis of clinical survival curves was performed to reveal the prognostic value of the crucial genes among HCC patients via the online web-tool GEPIA2 and KM plotter. Results: 5510 DEGs associated with non-fibrosis NAFLD, 3913 DEGs about NAFLD fibrosis, and 739 DEGs related to NAFLD progression from mild fibrosis to advanced fibrosis were identified. Then, a total of 112 common DEGs were found. The result of enrichment analyses suggested that common DEGs were strongly associated with the glucocorticoid receptor pathway, regulation of transmembrane transporter activity, peroxisome, and proteoglycan biosynthetic process. Six genes, including KIAA0101, NUSAP1, UHRF1, RAD51AP1, KIF22, and ZWINT, were identified as crucial candidate genes via the PPI network. The expression of ZWINT, NUSAP1 and KIAA0101 was validated highly expressed in vitro and vivo NAFLD models. Finally, we found that NUSAP1 was also significantly regulated at transcriptional and protein levels and associated with poor survival and advanced tumor stage among HCC patients. Conclusion: NUSAP1 may be a potential therapeutic target for preventing NAFLD progression to liver cancer.